Analisis Manajemen Kompensasi dalam Meningkatkan Motivas dan Kinerja SDI di Perusahaan Petis HJ. Diya Food Sampang - Abd Rohim; Rudy Haryanto (Al-Hiwalah: Journal of Sharia Economic Law, 2023)
Human Resource Performance or commonly known as an actual performance is a result achieved by a person in fulfilling his responsibilities as an employee. To produce good performance, of course, a way is needed so that the stake holder can work optimally. The existence of compensation in an organization or company can support motivational work so that it can produce good performance. This happened precisely at the petis Hj. Diya Food company, exactly on Jl. Mutiara Sampang which applies compensation to support employees’ enthusiasm. The purpose of this study is to explain the strategy of the petis Hj. Diya Food company in managing compensation so that it has an impact on the motivation of employee performance. The design of this study uses qualitative research with data collection techniques through observations, interviews, and documentations. Researcher analyzed the data using qualitative descriptive techniques. The results of this study showed that compensation has an impact on the motivation of workers in the company of petis Hj. Diya Food Sampang in producing good performance.